Tent encampment at the mouth of Pelly River, Yukon Territory, 1898. - Hegg, Eric A., 1867-1948 (1898)
Caption on image: "Mouth of Pelly River c. 1898" Original photograph by Hegg 3197; copied by Larss and Duclos.